2021
DOI: 10.1002/msc.1575
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of educational needs among patients with inflammatory arthritis

Abstract: Introduction: Patient education is important in the follow-up and disease management for patients with chronic inflammatory arthritis. Patients' needs for education and information varies, and it is important that the education is tailored to the individual patient. Hence, the aim of this study is to investigate whether patients' educational needs change over time, and which demographic, disease-related or self-management characteristics that are associated with patients' educational needs. Methods:The Mann-Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…As hope is a multidimensional and dynamic life force, it may facilitate an individual's psychological adjustment by influencing appraisal and coping strategies (Wu et al, 2021). This result is supported by some recent trajectory analyses in orthopaedic or surgical populations that showed that the level of hope significantly predicted fatigue symptoms in patients with rheumatoid arthritis (Xu et al, 2017) and psychological resilience in patients with orthognathic surgery (Grønning et al, 2021). However, an unrealistic expectation of surgical recovery is a common phenomenon in orthopaedic surgery, even though evidence-based practice guidelines have clearly pointed out that some factors may influence an individual's recovery from surgery (van Doormaal et al, 2020).…”
Section: Predictors Of the Different Classesmentioning
confidence: 68%
See 2 more Smart Citations
“…As hope is a multidimensional and dynamic life force, it may facilitate an individual's psychological adjustment by influencing appraisal and coping strategies (Wu et al, 2021). This result is supported by some recent trajectory analyses in orthopaedic or surgical populations that showed that the level of hope significantly predicted fatigue symptoms in patients with rheumatoid arthritis (Xu et al, 2017) and psychological resilience in patients with orthognathic surgery (Grønning et al, 2021). However, an unrealistic expectation of surgical recovery is a common phenomenon in orthopaedic surgery, even though evidence-based practice guidelines have clearly pointed out that some factors may influence an individual's recovery from surgery (van Doormaal et al, 2020).…”
Section: Predictors Of the Different Classesmentioning
confidence: 68%
“…Therefore, this difference between the above variables might be masked by other predictors. For example, in a previous study, social support and positive psychological resources in patients with arthritis were predictors of psychological resilience (Smith & Zautra, 2008), while considering the characteristics of chronic degenerative knee disease and rehabilitation after surgery, patients need more self‐management education and accessibility to local health resources (Grønning et al, 2021). Therefore, education level and the distribution and accessibility of medical resources are the key components of self‐management and social support and seem to be more significant to psychological resilience.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation